Moving Upstream in U.S. Hospital Care Toward Investments in Population Health. Issue 5 (September 2017) - Begun, James W.; Potthoff, Sandra
Abstract : EXECUTIVE SUMMARY: The root causes for most health outcomes are often collectively referred to as the social determinants of health. Hospitals and health systems now must decide how much to "move upstream, " or invest in programs that directly affect the social determinants of health. Moving upstream in healthcare delivery requires an acceptance of responsibility for the health of populations. We examine responses of 950 nonfederal, general hospitals in the United States to the 2015 American Hospital Association Population Health Survey to identify characteristics that distinguish those hospitals that are most aligned with population health and most engaged in addressing social determinants of health. Those "upstream" hospitals are significantly more likely to be large, not-for-profit, metropolitan, teaching-affiliated, and members of systems. Internally, the more upstream hospitals are more likely to organize their population health activities with strong executive-level involvement, full-time-equivalent support, and coordination at the system level. The characteristics differentiating hospitals strongly involved in population health and upstream activity are not unlike those characteristics associated with diffusion of many innovations in hospitals. These hospitals may be the early adopters in a diffusion process that will eventually include most hospitals or, at least, most not-for-profit hospitals. Alternatively, the population health and social determinants movements could be transient or could be limited to a small portion of hospitals such as those identified here, with distinctive patient populations, missions, and resources.